Three-Dimensional Numerical Simulation of Droplet Evaporation Using the Lattice Boltzmann Method Based on GPU-CUDA Accelerated Algorithm (Communications in Computational Physics, 2020)
The three-dimensional (3D) single component multiphase Shan-Chen latticeBoltzmann (LB) model is implemented with the GPU-accelerated algorithm based onthe CUDA platform for the simulation of droplet evaporation. It is found that thespeed-up of the GPU-accelerated 3D LB model with respect to the CPU-based 3D LBmodel increases with the computational node number. The maximum speed-up ishigher than around 300 when the computational domain is composed of $256^3$ computationalnodes. Regarding the calculations performed using the GPU-accelerated3D LB model that incorporates the operation of data output through CPU, the percentageof computational time consumed by CPU for executing the sequential tasksincreases with the computational node number. The model validations are carried outthrough the comparisons of the simulations with Laplace's law and the $D^2$ law. Then,the GPU-accelerated 3D LB model is applied to simulate the evaporation phenomenaof a droplet laying on smooth and rough solid surfaces. It is shown that the contact angleof the evaporating droplet on a smooth solid surface almost remains stable duringthe evaporation process. For the evaporating droplet sitting on a rough solid surface,however, the time evolution of the contact angle displays obvious oscillations. Thesimulated morphology evolution of the evaporating droplet sitting on a rough solidsurface demonstrates that the oscillations of the contact angle are governed by thestick-slip movement, namely, depinning and receding, of the liquid-gas-solid contactline. This can be attributed to the large hysteresis of the droplet displaying the wettingWenzel state.